2020
DOI: 10.1111/nyas.14337
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding large‐scale responses of the water cycle to climate change

Abstract: Globally, thermodynamics explains an increase in atmospheric water vapor with warming of around 7%/°C near to the surface. In contrast, global precipitation and evaporation are constrained by the Earth's energy balance to increase at ∼2-3%/°C. However, this rate of increase is suppressed by rapid atmospheric adjustments in response to greenhouse gases and absorbing aerosols that directly alter the atmospheric energy budget. Rapid adjustments to forcings, cooling effects from scattering aerosol, and observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
210
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(227 citation statements)
references
References 358 publications
(424 reference statements)
13
210
1
3
Order By: Relevance
“…Within the latest studies using global coupled models, there is a widespread consensus that the Indian monsoon rainfall will increase due to climate change in the 21st century (Chaturvedi et al, 2012;Menon et al, 2013;Lee and Wang, 2014;Asharaf and Ahrens, 2015;Mei et al, 2015;Sharmila et al, 2015;Varghese et al, 2020). This trend is found for various Coupled Model Intercomparison Project phase 5 (CMIP5) models (Menon et al, 2013), the multi-model mean (Chaturvedi et al, 2012), the mean of only the four best models (Lee and Wang, 2014) or the model with the best deep convection scheme (Varghese et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Within the latest studies using global coupled models, there is a widespread consensus that the Indian monsoon rainfall will increase due to climate change in the 21st century (Chaturvedi et al, 2012;Menon et al, 2013;Lee and Wang, 2014;Asharaf and Ahrens, 2015;Mei et al, 2015;Sharmila et al, 2015;Varghese et al, 2020). This trend is found for various Coupled Model Intercomparison Project phase 5 (CMIP5) models (Menon et al, 2013), the multi-model mean (Chaturvedi et al, 2012), the mean of only the four best models (Lee and Wang, 2014) or the model with the best deep convection scheme (Varghese et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 was identified as the causative agent of COVID-19 (Wu et al, 2020) and similar to SARS coronavirus, it uses ACE2 as the primary cellular entry receptor (Hoffmann et al, 2020; Li et al, 2003). SARS-CoV-2 has a tropism for the upper airways and the lung (Wölfel et al, 2020), despite rather low numbers of cells that co-express ACE2 and the essential cofactor for ACE2 binding, TMPRSS2 (Allan et al, 2020; Qi et al, 2020; Sungnak et al, 2020; Ziegler et al, 2020), but the expression of ACE2 and TMPRSS2 in airway epithelial cells are increased by type-I IFN stimulation (Ziegler et al, 2020). Single cell studies of bronchoalveolar lavage samples have suggested a complex dysregulation of the pulmonary immune response in severe COVID-19 (Liao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Peak P intensities were markedly higher at low latitudes (<30°N/S; Fig. 2b), due to the higher air temperatures which lead to more intense P in accordance with the Clausius-Clapeyron relationship [55][56][57] . The highest 15-year return-period P intensities (>200 mm d −1 ) over land were found in parts of Central America, India, and Southeast Asia, along the western equatorial coast of Africa, and over oceans in the intertropical convergence zone (Fig.…”
mentioning
confidence: 60%